Synthesis and Antimicrobial Activity of Lysichitalexin - Vanisree, Mulabagal; Jayalakshmi, Ravi; V. Subbaraju, Gottumukkala (Asian Journal of Chemistry, 2010)
Lysichitalexin [2-(4-methoxyphenyl)-1-nitroethane] 1, a stress induced metabolite from Lysichitum americanum, has been synthesized starting from 4-methoxybenzaldehyde in two steps with an overall yield of 64%. The intermediate product, 2-(4-methoxyphenyl)-1-nitroethene 3 showed excellent antimicrobial acitvity.